The patriarch : the remarkable life and turbulent times of Joseph P. Kennedy - Nasaw, David (Penguin Press, 2012)
"Celebrated historian David Nasaw brings to life the story of Joseph Patrick Kennedy, in this, the first and only biography based on unrestricted and exclusive access to the Joseph P. Kennedy papers."--